Impact of Behavioral Feeding Intervention on Child Emotional and Behavioral Functioning, Parenting Stress, and Parent-Child Attachment. Issue 3 (September 2019) - Knight, Rachel M.; Albright, Jeremy J.; Huth-Bocks, Alissa; Morris, Natalie K.; Mills, Lauren; Klok, Kaylin; Kallabat, Nora; Drayton, Amy K.
ABSTRACT: Objectives: Behavioral intervention is the only treatment for pediatric feeding problems with well documented empirical support. However, parents may be hesitant to pursue behavioral intervention because of concerns about possible negative side effects on child behavioral health and the parent-child relationship. This study investigated associations between behavioral feeding treatment and parenting stress, internalizing and externalizing behavior problems in young children, and parent-child attachment quality. Methods: Participants included 16 mother-child dyads seeking treatment from a behavioral feeding clinic at a large Midwestern university medical center. Children were between the ages of 30 and 45 months (adjusted) at baseline. Caregivers completed the Child Behavior Checklist for ages 1.5 to 5 (CBCL/1.5–5), the Parenting Stress Index, 3rd Edition Short Form (PSI/SF), and mother-child dyads participated in the Strange Situation procedure at baseline and again after 6 months. The treatment group ( n  = 12) began outpatient behavioral feeding intervention following the baseline evaluation, whereas the control group ( n  = 12) remained on the clinic waitlist until after the 6-month follow-up. Results: The treatment group demonstrated decreases in internalizing and externalizing child behavior problems and parenting stress compared with the control group. No significant differences were demonstrated in parent-child attachment quality within or between groups. Conclusions: Behavioral feeding intervention had positive effects on perceptions of child emotional and behavioral functioning and maternal parenting stress. Intervention also did not impact the quality of the mother-child attachment relationship. Further research with a larger sample size and additional observational measures of behavior is needed to support the replicability and generalizability of these results.